2021
DOI: 10.1021/acs.jafc.1c00088
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Study of the Insecticidal Activity of Novel Steroidal 1,3,4-Oxadiazoles

Abstract: A series of novel steroidal derivatives with a substituted 1,3,4-oxadiazole structure was designed and synthesized, and the target compounds were evaluated for their insecticidal activity against five aphid species. Most of the tested compounds exhibited potent insecticidal activity against Eriosoma lanigerum (Hausmann), Myzus persicae, and Aphis citricola. Compounds 20g and 24g displayed the highest activity against E. lanigerum, showing LC50 values of 27.6 and 30.4 μg/mL, respectively. Ultrastructural change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Naturally, insecticidal agents control insects through a variety of mechanisms, including contact, stomach, repellent, fumigant, and systemic methods or through food intake prevention or oviposition inhibition, etc. [ 40 , 49 , 51 ]. Zhang et al (2013) found that the A. vera L. leaf acetone extract had contact acaricidal, repellent, fumigant, and oviposition inhibitory activities against T. cinnabarinus [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Naturally, insecticidal agents control insects through a variety of mechanisms, including contact, stomach, repellent, fumigant, and systemic methods or through food intake prevention or oviposition inhibition, etc. [ 40 , 49 , 51 ]. Zhang et al (2013) found that the A. vera L. leaf acetone extract had contact acaricidal, repellent, fumigant, and oviposition inhibitory activities against T. cinnabarinus [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2013) found that the A. vera L. leaf acetone extract had contact acaricidal, repellent, fumigant, and oviposition inhibitory activities against T. cinnabarinus [ 51 ]. Ma et al (2021a) reported that 1,3,4-oxadiazoles possessed excellent contact activity and weak systemic activity against E. lanigerum [ 49 ]. Here, a study of the mode of action demonstrated that GC16 had contact activity against T. pueraricola , similar to the mite contact activity of botanical extracts from A. vera and Artemisia annua [ 51 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations